Esterilizaciones durante el gobierno de Alberto Fujimori: ¿política de planificación familiar o delitos dolosos y crímenes de lesa humanidad? - Montoya Vivanvo, Yván; Rodríguez Vásquez, Julio; Morales Nakandakari, Pamela; Prado, Bertha (Pontificia Universidad Católica del Perú, 2014)
Given the unresolved status of the cases of victims of forced sterilizations during the government of Alberto Fujimori, this report aims to identify criterias of rationality from criminal doctrine and jurisprudence developed over the years, that will enable judicial officers to get a fair decision, consistent with a Constitutional Democracy, when determining criminal responsibility.Also, with the review of Salomon Lerner and Yvan Montoya, renowned lawyers defenders of human rights and knowledgeable in the subject.

Ante la situación irresuelta de las denuncias de las victimas deesterilizaciones involuntarias durante el gobierno de Alberto Fujimori, el presente informe pretende identificar criterios de racionalidad provenientes de la doctrina y jurisprudencia penal que le permitan a los operadores judiciales obtener una decisión justa y acorde a una Democracia Constitucional, al momento de determinar la responsabilidad penal.Asimismo, se cuenta con los comentarios del Dr. Salomón Lerner y Dr. Yvan Montoya, reconocidos abogados defensores de los derechos humanos y entendidos en el tema.
Sterilizations during the Alberto Fujimori’s government: family planning policy or intentional crimes and crimes against humanity?
Keywords: Law; Involuntary Sterilization; Serious Injury; Homicide; Intent; Crime Against Humanity; Esterilizaciones Involuntarias; Lesiones Graves; Homicidio; Dolo; Autoría Mediata; Crimen de Lesa Humanidad; https://purl.org/pe-repo/ocde/ford#5.05.00